Heterotrigona itama Pollen Analysis as a Bioindicator of Floral Diversity in South Kalimantan Oil Palm Agroforestry - Kadarsah, Anang; Ulimaz, Almira; Yardani, Jesi; Satriadi, Trisnu; Ogbodo, John Agbo (Biosaintifika: Journal of Biology & Biology Education, 2025)
Background: The expansion of oil palm plantations in Indonesia drives deforestation and biodiversity loss, threatening pollinator communities. Agroforestry systems within oil palm landscapes may enhance floral resources, but their effectiveness is poorly understood. This study evaluates the potential of stingless bee (Heterotrigona itama) pollen analysis as a tool for monitoring floral diversity in different oil palm agroforestry systems. Methods: Pollen samples were collected from H. itama colonies in five distinct oil palm agroforestry systems (block-type, intercropping, row-type, fence-type, and palm oil-livestock) across South Kalimantan. Pollen types were identified microscopically, and diversity metrics (Shannon Index, Simpson Index, and Evenness) were calculated to assess foraging patterns and floral resource availability. Results: Analysis identified 30 plant species from 22 families. Agroforestry type significantly influenced pollen composition. Block-type systems exhibited the highest species richness (14 types), while fence-type systems showed the lowest (9 types) with heavy dominance by maize (Zea mays, 41.4%). Intercropping systems were dominated by Acacia mangium (51.2%). Row-type systems demonstrated the most balanced foraging (highest evenness). A moderate Sørensen similarity index (0.63) between pollen and field vegetation confirmed bees as effective samplers of landscape floral diversity. This research confirms that H. itama pollen analysis is an efficient bioindicator tool, revealing that agroforestry management directly shapes pollinator resource availability. Complex systems (e.g., block-type, row-type) support higher floral diversity, which is crucial for pollinator conservation and sustainable productivity in oil palm-dominated landscapes. This method provides a practical approach for guiding biodiversity-inclusive agricultural practices.